Specificity of social adaptation of university teachers approaching retirement age - Denis Vladimirovich Fedosyuk (Вестник Майкопского государственного технологического университета)
The article presents a sociological analysis of a topical research problem related to the study of the specifics of social adaptation of university teachers of pre-retirement age. A focused interview method was used (a qualitative strategy was used). The respondents were university professors aged 58 to 64 (women and men, respectively, of pre-retirement age). The research was of a pilot nature; it pursued the goal of collecting preliminary primary information on the problem of social adaptation of teachers of pre-retirement age working in higher educational institutions. As a result of the study, the following results were achieved: respondents are much more concerned about the difficulties of adapting to the status of a «teacher of pre-retirement age» than to the changes in their health status; the overwhelming majority of respondents would like to continue their professional activities when they reach retirement age; the main factor influencing the fulfillment of the obligatory scientometric indicators by teachers is a favorable moral and psychological climate in the work collective and cooperation between members of the teaching staff of different age groups. The potential of personnel development in the higher education system is, among other things, in the successful social and professional adaptation and cooperation of teachers with different teaching experience.